Stimulatory effect of fluoxetine and desipramine, but not mirtazapine on C26 colon carcinoma hepatic metastases formation: association with cytokines - Kubera, Marta; Arteta, Beatriz; Grygier, Beata; Curzytek, Katarzyna; Malicki, Stanisław; Maes, Michael (Frontiers in Immunology, 2023)
Due to the high prevalence of depression among cancer patients, antidepressant medications are frequently administered as adjuvant treatment. However, the safety of such medications in the development of metastasis is unclear. In this study, we investigated the effects of fluoxetine, desipramine, and mirtazapine on the liver metastasis of murine C26 colon carcinoma (cc). Balb/c male mice were administered these antidepressants intraperitoneally (i.p.) for 14 days following intrasplenic injections of C26 colon carcinoma cells. Desipramine and fluoxetine, but not mirtazapine, significantly increased the number of tumor foci and total volume of the tumor in liver tissue. This effect was associated with a decrease in the ability of splenocytes to produce interleukin (IL)-1β and interferon (IFN)-γ and an increase in their ability to produce interleukin (IL)-10. Similar changes were observed in plasma IL-1β, IFN-γ, and IL-10 levels. The current study demonstrates that the stimulatory effect of desipramine and fluoxetine, but not mirtazapine, on experimental colon cancer liver metastasis is associated with a suppression of immune defenses against the tumor.